"Living With a Ball and Chain": The Experience of Stroke for Individuals and Their Caregivers in Rural Appalachian Kentucky. Issue 4 (23rd May 2013) - Danzl, Megan M.; Hunter, Elizabeth G.; Campbell, Sarah; Sylvia, Violet; Kuperstein, Janice; Maddy, Katherine; Harrison, Anne
Abstract Purpose Individuals in rural Appalachian Kentucky face health disparities and are at increased risk for negative health outcomes and poor quality of life secondary to stroke. The purpose of this study is to describe the experience of stroke for survivors and their caregivers in this region. A description of their experiences is paramount to developing tailored interventions and ultimately improving health care and support. Methods An interprofessional research team used a qualitative descriptive study design and interviewed 13 individuals with stroke and 12 caregivers, representing 10 rural Appalachian Kentucky counties. The transcripts were analyzed using qualitative content analysis. Findings A descriptive summary of the participants' experience of stroke is presented within the following structure: (1) Stroke onset, (2) Transition through the health care continuum (including acute care, inpatient rehabilitation, and community‐based rehabilitation), and (3) Reintegration into life and rural communities. Conclusions The findings provide insight for rural health care providers and community leaders to begin to understand the experience of stroke in terms of stroke onset, transition through the health care continuum, return to home, and community reintegration. An understanding of these experiences may lead to discussions of how to improve service provision, facilitate reintegration, support positive health outcomes, and improve quality of life for stroke survivors and their caregivers. The findings also indicate areas in need of future research including investigation of the effects of support groups, local health navigators to improve access to information and services, involvement of faith communities, proactive screening for management of mental health needs, and caregiver respite services.